Mast Cell Profile in Benign and Malignant Prostatic Lesions - Das, Bismay; D, Sumanth (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Mast cells have an important role in innate and adaptive immunity. There role in tumour pathology is under investigation due to studies linking them to angiogenesis, tissue remodeling and stromal immunomodulation. Reports suggest that they can exert both pro or anti tumour effects. The role of mast cells may be influenced by its location in the lesion. In the present study, the number and distribution of mast cells in both benign and malignant prostatic lesions were recorded. Methodology: Fifty seven patients of benign prostatic hyperplasia (BPH) and 43 patients of adenocarcinoma (Ca) were the subjects of the study. Inflammatory conditions of prostate like prostatitis and other malignancies of prostate like sarcoma, transitional cell carcinoma etc were excluded from the study. This was a descriptive study with purposive sampling. Histological diagnosis was made by examining sections stained with Haematoxylin and Eosin. Additional sections from the same block were stained for mast cells using Giemsa stains as per standard protocol. Mast cell count was done in minimum 6 random high power microscopy field in four different regions viz., intraglandular, periglandular, stromal and perivascular regions for BPH and intratumoral, peritumoral, stromal and perivascular regions for Ca. Results were analysed statistically. Results: In BPH cases showed a significantly higher number of mast cells in stromal as well as periglandular areas followed by perivascular area. Only few mast cells were observed in intraglandular area. Similar was the observations in adenocarcinoma cases where the maximum number of mast cells were concentrated in the stromal and perilesional area. The number of mast cells in stroma of BPHwas higher as compared to that of adenocarcinoma. In rest of the areas, the numbers were comparable. Conclusion: This study showed no remarkable difference in the number and distribution of mast cells in benign and malignant prostatic lesions. There is paucity of such studies in the literature and the possible utility of mast cell count to differentiate malignant from benign and atypical conditions needs further evaluation.